Pengaruh Penerapan Model Discovery Learning pada Pembelajaran Bermuatan IPA Terhadap Hasil Belajar Siswa Kelas III SDN 1 Ploso - Rizki Setya Kartika; Sukamti Sukamti; Esti Untari; Rizki Setya Kartika; Sukamti Sukamti (Universitas Negeri Malang, 2023)
Abstract: This research was conducted to determine whether or not the implementation of the Discovery Learning model had an influence on the learning outcomes of the cognitive aspects of class III students at SDN 1 Ploso, Pacitan District. A quantitative approach using the experimental method is used in this study. The population and sample in this study were 42 students where class IIIA was the control class and IIIB was the experimental class. Tests and documentation are data collection techniques in this study. Instrument testing techniques include validity test, reliability test, level of difficulty and differential power. Prerequisite test t-test and hypothetical test are the data analysis techniques used. Prerequisite test through normality test, linearity test and homogeneity test. In order to find out whether there is a difference in the pretest-posttest average scores of the two classes, a t-test is carried out. The hypothesis test is in the form of a simple linear regression test where the result is a significance value of 0.000 <0.05, so it can be concluded that the application of the Discovery Learning model has an effect on the learning outcomes of the cognitive aspects of class III students at SDN 1 Ploso. Abstrak: Penelitian ini dilakukan guna mengetahui terdapat pengaruh atau tidak pelaksanaan model Discovery Learning terhadap hasil belajar aspek kognitif siswa kelas III SDN 1 Ploso, Kecamatan Pacitan. Pendekatan kuantitatif bermetode eksperimen digunakan di penelitian ini. Populasi dan sampel pada penelitian ini yakni sebanyak 42 siswa dimana kelas IIIA merupakan kelas kontrol dan IIIB merupakan kelas eksperimen. Tes serta dokumentasi merupakan teknik pengumpulan data pada penelitian ini. Teknik pengujian instrumen diantaranya uji validitas, uji reliabilitas, tingkat kesukaran dan daya beda. Uji prasyarat uji-t, dan uji hipotesis merupakan teknik analisis data yang dipakai. Uji prasyarat melalui uji normalitas, uji linearitas dan uji homogenitas. Guna mengetahui ada tidaknya beda nilai rata-rata pretest-posttest kedua kelas dilaksanakan uji-t. Uji hipotesis berupa uji regresi linear sederhana dimana hasil nilai signifikansi sebesar 0,000 < 0,05 maka bisa diambil kesimpulan jika penerapan model Discovery Learning berpengaruh terhadap hasil belajar aspek kognitif siswa kelas III SDN 1 Ploso.